Modeling of pneumococcal serogroup 10 capsular polysaccharide molecular conformations provides insight into epitopes and observed cross-reactivity - Richardson, Nicole I.; Kuttel, Michelle M.; Ravenscroft, Neil (Frontiers in Molecular Biosciences, 2022)
Streptococcus pneumoniae is an encapsulated gram-negative bacterium and a significant human pathogen. The capsular polysaccharide (CPS) is essential for virulence and a target antigen for vaccines. Although widespread introduction of pneumococcal conjugate vaccines (PCVs) has significantly reduced disease, the prevalence of non-vaccine serotypes has increased. On the basis of the CPS, S. pneumoniae serogroup 10 comprises four main serotypes 10A, 10B, 10C and 10F; as well as the recently identified 10D. As it is the most prevalent, serotype 10A CPS has been included as a vaccine antigen in the next generation PCVs. Here we use molecular modeling to provide conformational rationales for the complex cross-reactivity reported between serotypes 10A, 10B, 10C, and 10F anti-sera. Although the highly mobile phosphodiester linkages produce very flexible CPS, shorter segments are conformationally defined, with exposed β-D-galactofuranose (βDGalf) side chains that are potential antibody binding sites. We identify four distinct conformational epitopes for the immunodominant βDGalf that assist in rationalizing the complex asymmetric cross-reactivity relationships. In particular, we find that strongly cross-reactive serotypes share common epitopes. Further, we show that human intelectin-1 has the potential to bind the exposed exocyclic 1,2-diol of the terminal βDGalf in each serotype; the relative accessibility of 3- or 6-linked βDGalf may play a role in the strength of the innate immune response and hence serotype disease prevalence. In conclusion, our modeling study and relevant serological studies support the inclusion of serotype 10A in a vaccine to best protect against serogroup 10 disease.